An Elementary Approach on Hyperconnected Spaces - et. al., D.Sasikala, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper aims to establish a new notion of hyperconnected spaces namely semi j hyperconnected spaces by using semi j open sets. The relation between the existing spaces are also discussed. We also investigate some elementary properties of semi j hyperconnected spaces.